218k views
2 votes
Select the vertical asymptote(s) of the function
f(x)=((x+6)(x-1))/((x-2)(x+6))

A. x=2
B. x=-6
C. x=2, x=-6
D. x=-2

2 Answers

6 votes

Answer:

A. x = 2

Explanation:

(x+6)(x-1) รท (x-2)(x+6)

Since x+6 is common to both, numerator and denominator, it will get cancelled out

And there will be a hole at x = -6

The simplified form would be

(x-1)/(x-2)

There will be a vertical asymptote at x = 2, because the denominator becomes zero at x = 2

User Noor Ahmed
by
4.5k points
5 votes

Answer:

As the described function, we want to find vertical asymtotes, we find the value of x so that the denominator is equal to 0.

Here, (x - 2)(x + 6) = 0

=> x = 2, x =-6

=> Option C is correct.

Hope this helps!

:)

User Javier Sivianes
by
5.0k points